Ultrafast core-excited electron dynamics in model crystalline organic semiconductors. Issue 3 (20th December 2019) - Duong, Vincent V.; Prendergast, David; Ayzner, Alexander L.
Abstract : Resonant photoemission measurements show that ultrafast electron dynamics in core-excited states of large organic semiconductors depends on both the nature of the core-hole and the proximal chemical environment. Abstract : Electron transfer is key to the operation of devices based on molecular (organic) semiconductors. Others have shown that electron transfer in the solid state often proceeds on sub-50 fs timescales, the details of which can be difficult to temporally resolve using pump–probe spectroscopy. A popular technique to measure average time scales for such rapid electron-transfer events is the core-hole clock implementation of resonant Auger electron spectroscopy at a single X-ray absorption edge. This is often done on relatively small molecules with core-excited states that are highly localized. We have used resonant Auger spectroscopy to probe sub-50 fs electron dynamics of two relatively large model organic semiconductors: Cu phthalocyanine (CuPc) along with its fluorinated analog, F16 CuPc. We have interrogated electron dynamics simultaneously at N and C K-edges, along with calculations of initial and final states participating in the core-excited states. Our measurements show that the electron dynamics differ substantially across the two absorption edges for a given molecule, and that there are significant differences at a given edge between the two derivatives. X-ray spectroscopy calculations suggest that the extension of π-electron density onto peripheral F atoms in F16 CuPc is implicated in the large change in ultrafast electron dynamics upon fluorination. We believe our results have important implications for analysis of core-hole clock measurements on relatively large organic semiconductors.